2020
DOI: 10.1021/acsptsci.9b00101
|View full text |Cite
|
Sign up to set email alerts
|

(S)-5-(2′-Fluorophenyl)-N,N-dimethyl-1,2,3,4-tetrahydronaphthalen-2-amine, a Serotonin Receptor Modulator, Possesses Anticonvulsant, Prosocial, and Anxiolytic-like Properties in an Fmr1 Knockout Mouse Model of Fragile X Syndrome and Autism Spectrum Disorder

Abstract: Fragile X syndrome (FXS) is a neurodevelopmental disorder characterized by intellectual disabilities and a plethora of neuropsychiatric symptoms. FXS is the leading monogenic cause of autism spectrum disorder (ASD), which is defined clinically by repetitive and/or restrictive patterns of behavior and social communication deficits. Epilepsy and anxiety are also common in FXS and ASD. Serotonergic neurons directly innervate and modulate the activity of neurobiological circuits altered in both disorders, providi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 90 publications
(174 reference statements)
4
43
0
Order By: Relevance
“…Moreover, the authors pursued thorough pharmacokinetic study and claimed that orally operative (+)-5-FPT appears to be a promising candidate for ASD treatment. The group re-evaluated pharmacokinetic values and further validated the effect of (+)-5-FPT in a genetic model, Fmr1 knockout, and wild-type mice [ 102 ]. In addition to providing anxiolytic-like effects, it significantly relieved repetitive behavior and enhanced social interaction both in wild-type and the transgenic mice.…”
Section: 5-ht 7 Receptor (5-ht 7 ...mentioning
confidence: 99%
“…Moreover, the authors pursued thorough pharmacokinetic study and claimed that orally operative (+)-5-FPT appears to be a promising candidate for ASD treatment. The group re-evaluated pharmacokinetic values and further validated the effect of (+)-5-FPT in a genetic model, Fmr1 knockout, and wild-type mice [ 102 ]. In addition to providing anxiolytic-like effects, it significantly relieved repetitive behavior and enhanced social interaction both in wild-type and the transgenic mice.…”
Section: 5-ht 7 Receptor (5-ht 7 ...mentioning
confidence: 99%
“…Taking all the following evidence into consideration, there is a strong demand for the development of novel 5-HT7R agonists with improved pharmacokinetic properties and activity. Armstrong and co-workers recently reported that treatment with the orally operative aminotetraline compound (+)-5-FPT [ 65 ], which is a partial agonist of 5-HT1A, 5-HT2C, and 5-HT7 receptors, leads to significant improvement in the phenotypic condition [ 78 ] ( Table 1 ). In particular, it considerably mitigated repetitive behavior, markedly reduced the occurrence of lethal audiogenic seizures, which are typical for Fmr1-KO condition, and elevated the social activity both in wild-type and FXS transgenic mice [ 78 ].…”
Section: Fragile X Syndrome (Fxs)mentioning
confidence: 99%
“…Armstrong and co-workers recently reported that treatment with the orally operative aminotetraline compound (+)-5-FPT [ 65 ], which is a partial agonist of 5-HT1A, 5-HT2C, and 5-HT7 receptors, leads to significant improvement in the phenotypic condition [ 78 ] ( Table 1 ). In particular, it considerably mitigated repetitive behavior, markedly reduced the occurrence of lethal audiogenic seizures, which are typical for Fmr1-KO condition, and elevated the social activity both in wild-type and FXS transgenic mice [ 78 ]. As well as 5-HT 1A R, 5-HT 2C R was shown to be involved in the activation of phospholipase C beta (PLCβ), protein kinase C (PKC), and, as a consequence, the mitogen-activated protein kinase/extracellular signal-regulated kinase (ERK/MAPK) signaling pathway, which is essential for normal cell functioning, and its alteration is detected in various neurological disorders [ 85 , 86 , 87 ].…”
Section: Fragile X Syndrome (Fxs)mentioning
confidence: 99%
“…The (+)-5-FPT potently attenuated stereotypy in three heterogeneous models of stereotypy in a mouse strain characterized by repetitive behavior . In 2020, the same research group reported that (+)-5-FPT was actually a 5-HT 1A R/5-HT 2C R agonist and 5-HT 7 R antagonist . This compound was then studied in a mouse model of Fragile X syndrome and found to reduce repetitive behavior through 5-HT 1A R partial agonism and to attenuate audiogenic seizure through 5-HT 2C R agonism.…”
Section: Introductionmentioning
confidence: 99%
“…26 In 2020, the same research group reported that (+)-5-FPT was actually a 5-HT 1A R/5-HT 2C R agonist and 5-HT 7 R antagonist. 27 This compound was then studied in a mouse model of Fragile X syndrome and found to reduce repetitive behavior through 5-HT 1A R partial agonism and to attenuate audiogenic seizure through 5-HT 2C R agonism. Thus, the potential of concomitant activation of 5-HT 1A R and 5-HT 7 R was not actually explored.…”
Section: ■ Introductionmentioning
confidence: 99%